Screening for Fetal Aneuploidy and Sex Chromosomal Anomalies in a Pregnant Woman With Mosaicism for Turner Syndrome—Applications and Advantages of Cell-Based NIPT - Jeppesen, Line Dahl; Hatt, Lotte; Singh, Ripudaman; Schelde, Palle; Andreasen, Lotte; Markholt, Sara; Lildballe, Dorte L.; Vogel, Ida (Frontiers in Genetics, 2021)
Background: Cell-free NIPT and cell-based NIPT are risk-free testing options using maternal blood samples to screen for fetal aneuploidies, but the methods differ. For cell-free NIPT, the fetal fraction of cell-free DNA in plasma is analyzed with a high background of maternal DNA. In contrast, for cell-based NIPT, a limited number of the rare, intact fetal cells are isolated for the genetic analysis. This case demonstrates the differences regarding testing for fetal sex-chromosomes anomalies (SCAs) between these two tests. Materials and Methods: A pregnant woman with mosaicism for Turner syndrome opted for NIPT in first trimester. For the cell-free NIPT analysis, DNA extraction, genome-wide massive parallel sequencing, and data analysis were carried out as described by the kit manufacturer (Illumina©, San Diego, CA, USA). For cell-based NIPT, the first sample gave no result, but the woman consented to repeat cell-based NIPT. After whole genome amplification and STR analysis, fetal DNA from three individual fetal cells was subjected to chromosomal microarray (aCGH, Agilent oligoarray,180 kb). Results: Fetal fraction was 7%, and cell-free NIPT showed 2 copies of chromosomes 13, 18 and 21 and a decreased proportion of chromosome X, suggestive of fetal Turner syndrome. In contrast, the cell-based NIPT result showed no aneuploidy and two X-chromosomes in the fetus. Conclusion: cell-based NIPT may provide a noninvasive testing option to screen for SCAs in women with mosaicism for monosomy-X in blood, where cell-free NIPT cannot discriminate whether the X-loss is maternal or fetal.